Diamond mars coating and its construction process
Patent Information
- Application Number
- CN202611231792.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-14
AI Technical Summary
[0006]针对以上问题,本发明提供一种钻石火星涂层及其施工工艺,用于解决目前光固化涂料用于木质基材制备钻石火星涂层时存在耐磨性偏差的问题
[0021]本发明提供的钻石火星涂层对应的底漆中采用以双(三羟甲基)丙烷-异佛尔酮二异氰酸酯为交联核心、分子结构中同时含有磺酸基团、有机硅氧烷侧链和多醚侧链的功能聚氨酯丙烯酸酯作为主要成膜树脂。其中,磺酸基团能够与超硬耐磨粉表面产生强极性相互作用,增强填料锚固;有机硅氧烷链段凭借其低表面能和优异润湿性,可优先迁移至无机粉体界面形成致密包覆层,有效防止粉体团聚沉降,有效提升储存稳定性;多醚链段则提供柔顺性和应力释放能力,赋予涂层良好的抗磨韧性。
Smart Images

Figure CN122790534B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials technology, specifically a diamond Mars coating and its construction process. Background Technology
[0002] With the increasing demands for surface performance of wood-based panels from modern home decoration, high-end wood product processing, and commercial space renovation industries, traditional coating systems are struggling to meet the stringent requirements of high-frequency use and high-wear environments. In the field of wood-based panel surface coating technology, hardness and abrasion resistance remain core indicators for evaluating coating performance. Traditional polyurethane and nitrocellulose lacquer systems suffer from inherent defects such as low hardness (typically 1H-2H), poor abrasion resistance, long curing cycles, and high VOC emissions. While ultraviolet (UV) curing technology has brought about rapid drying and environmental benefits, existing UV coatings still face two major bottlenecks: first, the high degree of cross-linking leads to increased coating brittleness, resulting in insufficient adhesion to wood substrates when combined with high-abrasion-resistant fillers; second, conventional fillers such as alumina and silica (with a Mohs hardness below 9) are no longer sufficient for ultra-high abrasion-resistant applications.
[0003] Against this technological backdrop, the industry has proposed the concept of "diamond spark coating". This coating uses diamond (Mohs hardness 10) micro powder as the core wear-resistant reinforcing phase, which not only greatly improves the scratch resistance, but also generates sparks (sparks) when the diamond particles rub violently against the abrasive during high-speed grinding and polishing, which is a direct representation of the coating's ultra-high hardness and wear resistance.
[0004] Diamond Mars coatings are typically composed of a primer and a topcoat. The primer is applied directly to the surface of the wood substrate, and its main functions are: ① to connect the porous wood substrate containing polar functional groups, providing interfacial adhesion and stress transition; ② to introduce ultra-hard, wear-resistant powders, achieving a gradient transition in coating hardness and preventing coating cracking caused by excessive hardness differences between the topcoat and the substrate. The topcoat, as the outermost layer of the coating system, is the "first line of defense" directly facing the harsh external environment. Its main functions are: ① to provide ultimate scratch and wear resistance with ultra-high hardness diamond and other powders as the core anti-wear phase; ② to act as the ultimate barrier against chemical erosion, resisting the penetration and swelling of cleaning agents, oil stains, organic solvents, etc.; ③ to effectively transfer and release the stress to the primer through a strong interlayer bond.
[0005] While existing primers using epoxy acrylates offer some polar adhesion, they become brittle after curing, failing to release the internal stress from the high-load inorganic powders. This makes them prone to cracking and peeling when the wood is impacted or deformed. Flexible polyurethanes, though able to alleviate stress, have low cohesive strength and poor solvent resistance, failing to provide a solid support base for the topcoat. Furthermore, existing primer resins lack strong interaction with the surfaces of diamond, silicon carbide, and other powders, resulting in uneven dispersion and weak bonding within the resin matrix. This hinders the formation of a continuous and effective abrasion-resistant skeleton, weakening the primer's own abrasion resistance and its load-bearing capacity for the topcoat. For the topcoat, to improve abrasion resistance, a large amount of ultra-hard powders such as diamond and silicon carbide needs to be added. However, these ultra-hard powders have low surface polarity and poor compatibility with conventional organic resins. Under impact or high-frequency friction, the powders easily detach from the resin matrix, causing a sharp decline in abrasion resistance over time, failing to realize the true abrasion-resistant potential of diamond. Summary of the Invention
[0006] To address the above problems, this invention provides a diamond Mars coating and its application process, which solves the problem of abrasion resistance deviation when using current UV-cured coatings to prepare diamond Mars coatings on wood substrates.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a diamond Mars coating, composed of a diamond Mars coating primer layer and a topcoat layer; wherein, the primer layer is obtained by UV curing of the primer, and the topcoat layer is obtained by UV curing of the topcoat; the primer is composed of the following components in parts by weight: 30-40 parts of functional polyurethane acrylate, 9-12 parts of epoxy acrylate, 25-36 parts of multifunctional acrylate monomer, 18-25 parts of superhard wear-resistant powder, and 4-5 parts of photoinitiator; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles; the multifunctional acrylate monomer is composed of trifunctional acrylate monomer and difunctional acrylate monomer; based on the total mass of the multifunctional acrylate monomer, the trifunctional acrylate monomer accounts for 30%-40%, and the difunctional acrylate monomer accounts for 60%-70%; the chemical structure of the functional polyurethane acrylate is as follows:
[0008] ;
[0009] The topcoat is composed of the following components in parts by weight: 50-60 parts of silicone-fluorine modified sulfonic acid photocurable resin, 11-16 parts of trifunctional acrylate monomer, 8-12 parts of difunctional acrylate monomer, 3-5 parts of monofunctional acrylate monomer, 12-16 parts of superhard wear-resistant powder, and 4-5 parts of photoinitiator; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 4-5:7-9:9-12, and the chemical structure of the silicone-fluorine modified sulfonic acid photocurable resin is as follows:
[0010] .
[0011] Preferably, the trifunctional acrylate monomer in the primer is composed of pentaerythritol ethoxylated triacrylate and trimethylolpropane propoxylated triacrylate in a mass ratio of (3~9):(1~5); the difunctional acrylate monomer is composed of tripropylene glycol diacrylate and ethoxylated bisphenol A diacrylate in a mass ratio of (5~7):(2~4).
[0012] Preferably, the pentaerythritol ethoxylated triacrylate is pentaerythritol ethoxy(5) triacrylate.
[0013] Preferably, the ethoxylated bisphenol A diacrylate is 10(ethoxy)bisphenol A diacrylate.
[0014] Preferably, the mass ratio of diamond particles, zirconium oxide particles and silicon carbide particles in the primer is (3~5):(5~9):(10~12).
[0015] Preferably, the average particle sizes of the diamond particles, zirconium oxide particles, and silicon carbide particles in the primer are 10~20μm, 20~40μm, and 20~40μm, respectively.
[0016] Preferably, the trifunctional acrylate monomer in the topcoat is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2 to 5:3; the difunctional acrylate monomer is dipropylene glycol diacrylate; and the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2 to 1:3.
[0017] Preferably, the average particle sizes of the diamond particles, zirconium oxide particles, and silicon carbide particles in the topcoat are 4~8μm, 10~16μm, and 10~16μm, respectively.
[0018] A construction process for a diamond Mars coating as described above includes the following steps: surface treatment of a wood substrate, then coating the treated wood substrate surface with the primer as described above, light curing followed by coating with the topcoat as described above, and light curing to obtain the diamond Mars coating.
[0019] Preferably, the coating amount of the primer is 60~100g / m². 2 The energy for UV curing is 100~200 mJ / cm. 2 The application rate of the topcoat is 18~35g / m². 2 The energy for UV curing is 450~550 mJ / cm. 2 .
[0020] Compared with existing technologies, the beneficial effects of the diamond Martian coating and its application process of the present invention are as follows:
[0021] The primer corresponding to the Diamond Mars coating provided by this invention uses a functional polyurethane acrylate as the main film-forming resin, with bis(trimethylol)propane-isophorone diisocyanate as the crosslinking core and containing sulfonic acid groups, organosiloxane side chains, and polyether side chains in its molecular structure. The sulfonic acid groups can generate strong polar interactions with the surface of the superhard wear-resistant powder, enhancing filler anchoring; the organosiloxane segments, due to their low surface energy and excellent wettability, can preferentially migrate to the inorganic powder interface to form a dense coating layer, effectively preventing powder agglomeration and sedimentation, and effectively improving storage stability; the polyether segments provide flexibility and stress release capabilities, giving the coating good wear resistance and toughness.
[0022] The topcoat corresponding to the Diamond Mars coating provided by this invention uses a silicone-fluorine modified sulfonic acid type photocurable resin as the base resin, with adamantane as the core skeleton and containing sulfonic acid groups, organosilicon segments, and organofluorine segments in its molecular structure. The rigid cage structure of adamantane endows the resin with high hardness and good thermal stability; the sulfonic acid groups can generate strong polar interactions with the surface of the superhard wear-resistant powder, enhancing the anchoring force of the filler; the silicon-oxygen bonds in the organosilicon segments have high bond energy and flexibility, which can form effective molecular chain entanglement and polar interactions at the interface between the coating and the primer layer, improving the wettability and adhesion anchoring force of the coating to the primer layer, while adjusting the flexibility and crosslinking density of the resin network, which helps to absorb and disperse external impacts and reduce the tendency of wear-resistant powder particles to de-adhede under stress; the organofluorine segments, due to the low polarization rate and surface free energy of the carbon-fluorine bonds, can preferentially migrate to the coating surface and internal micropore interface during the curing process, forming a dense low surface energy barrier, effectively blocking the penetration and swelling damage of organic solvent molecules, and endowing the coating with excellent solvent resistance.
[0023] The diamond Mars coating provided by this invention is formed by the composite curing of a primer and a topcoat. The two components exhibit a good synergistic compatibility effect at the molecular structure level, resulting in excellent overall performance. Firstly, the polyether side chains in the primer provide flexibility and stress release capabilities, while the adamantane rigid framework in the topcoat provides high hardness and scratch resistance, effectively avoiding brittle cracking caused by excessive hardness in a single coating or interlayer stress concentration caused by excessive hardness. Secondly, both the organosiloxane side chains in the primer and the organosilicon segments in the topcoat contain silicon-oxygen bonds, exhibiting similar chemical composition and compatibility. This good affinity helps improve the interfacial bonding force between them. Thirdly, the sulfonic acid groups in both the primer and topcoat exert a polar anchoring effect on the ultra-hard wear-resistant powders in their respective layers, ensuring that fillers such as diamond and silicon carbide are firmly fixed in both the bottom and top layers. In particular, the low surface energy characteristics of the organofluorine segments in the topcoat further enhance the interfacial compactness of the powder coating. Finally, the primer provides filler anchoring and stress transition, while the topcoat provides surface hardness and a chemical barrier. Together, they enable the overall coating to have good adhesion and abrasion resistance on the wood substrate. Attached Figure Description
[0024] Figure 1 The above is the 1H NMR spectrum of the methacrylate phosphoryl chloride intermediate prepared in Example 1 of this invention;
[0025] Figure 2 The above is the 1H NMR spectrum of the siloxane monohydroxy intermediate prepared in Example 1 of this invention;
[0026] Figure 3 The above is the 1H NMR spectrum of the polyether monohydroxy intermediate prepared in Example 1 of this invention;
[0027] Figure 4 The 1H NMR spectrum of the functional polyurethane acrylate prepared in Example 1;
[0028] Figure 5 The above is the 1H NMR spectrum of the diacrylate hydroxyl compound intermediate prepared in Example 1 of this invention;
[0029] Figure 6 The above is the 1H NMR spectrum of the diacrylate phosphoryl chloride intermediate prepared in Example 1 of this invention;
[0030] Figure 7 The above is the 1H NMR spectrum of the diacrylate siloxane monohydroxy intermediate prepared in Example 1 of this invention;
[0031] Figure 8 The above is the 1H NMR spectrum of the diacrylate fluoroether monohydroxy intermediate prepared in Example 1 of this invention;
[0032] Figure 9The 1H NMR spectrum of the silicone-fluorine modified sulfonic acid photocurable resin prepared in Example 1 of this invention;
[0033] Figure 10 The image shows the diamond Martian coating of Example 1 before the abrasion resistance test.
[0034] Figure 11 This is an image of the diamond Martian coating of Example 1 after a wear resistance test. Detailed Implementation
[0035] To enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below with reference to embodiments. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way.
[0036] Example 1
[0037] The diamond Mars coating of this embodiment is composed of a diamond Mars coating primer layer and a topcoat layer; the diamond Mars coating primer layer is made of a UV-cured diamond Mars coating primer, and the topcoat layer is made of a UV-cured diamond Mars coating topcoat.
[0038] The primer for photocurable diamond Mars coating is composed of the following components in parts by weight: 30 parts functional polyurethane acrylate, 9 parts epoxy acrylate, 8 parts trifunctional acrylate monomer, 17 parts difunctional acrylate monomer, 18 parts superhard wear-resistant powder, and 4 parts photoinitiator; the trifunctional acrylate monomer is composed of pentaerythritol ethoxy(5) triacrylate and trimethylolpropanepropoxy(3) triacrylate in a mass ratio of 3:1; the difunctional acrylate monomer is composed of... The mixture consists of tripropylene glycol diacrylate and 10(ethoxy)bisphenol A diacrylate in a 5:2 ratio; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a 3:5:10 mass ratio, with average particle sizes of 10 μm, 20 μm, and 20 μm for the diamond, zirconium oxide, and silicon carbide particles, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a 2:1 mass ratio; and the epoxy acrylate is EBECRYL 600. The preparation method of the functional polyurethane acrylate is as follows:
[0039] (1) Under nitrogen protection, add 1.2 mol of phosphorus oxychloride and 600 mL of dichloromethane to a dry reaction flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Turn on the stirrer and cool down to 0℃. Dissolve 1.0 mol of 3-hydroxypropanesulfonic acid in 300 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 5℃. After the addition is complete, continue stirring the reaction at 0℃ for 3 h. After the reaction is complete, remove the solvent and unreacted phosphorus oxychloride under reduced pressure at 45℃ to obtain the intermediate 3-sulfonic acid propyl phosphate diacyl chloride.
[0040] The intermediate 3-sulfonyl propyl phosphate diacyl chloride, 400 mL of anhydrous dichloromethane, and 100 mL of anhydrous tetrahydrofuran were added to a reaction flask. After stirring until homogeneous, the mixture was cooled to 0°C. 1.0 mol of hydroxyethyl methacrylate and 2.2 mol of the acid-binding agent triethylamine were dissolved in 180 mL of anhydrous dichloromethane and then added dropwise to the reaction solution. The dropping rate was controlled, and the reaction temperature was maintained between 0 and 5°C. After the addition was complete, the mixture was stirred at 0°C for 6 hours. After the reaction was completed, the mixture was filtered under nitrogen protection while cold. The filtrate was then concentrated by vacuum distillation at 35°C to a volume equal to [amount missing] of the filtrate. 1 / 3 of the solution was added to obtain a concentrated solution. Under stirring, the concentrated solution was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath, stirred for 15 min, and allowed to stand for 2 h. The lower viscous phase was separated, and the upper petroleum ether supernatant was discarded. 20 mL of dichloromethane was added to the lower viscous phase, and after thorough stirring, 100 mL of anhydrous petroleum ether was added. After stirring and standing, the lower viscous phase was separated. The lower viscous phase was concentrated under reduced pressure to constant weight under nitrogen protection, at 35°C and a vacuum degree ≤-0.095 MPa to obtain the methacrylate phosphoryl chloride intermediate. The 1H NMR spectrum of the methacrylate phosphoryl chloride intermediate is shown below. Figure 1 As shown, the chemical structure is as follows:
[0041] .
[0042] (2) Under nitrogen protection, 0.06 mol of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane, 80 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The temperature was lowered to 0°C. 0.06 mol of methacrylate phosphoryl chloride intermediate was dissolved in 35 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature at 0~5°C. After the addition was complete, the temperature was naturally raised to room temperature, and the reaction was stirred for 6 h. After the reaction was completed, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤-0.095 MPa to obtain the siloxane monohydroxy intermediate. The chemical structure of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane is as follows:
[0043] ;
[0044] The 1H NMR spectrum of the siloxane monohydroxy intermediate is shown below. Figure 2 As shown, the chemical structure is as follows:
[0045] .
[0046] Under nitrogen protection, 0.06 mol of tetraethylene glycol, 80 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The mixture was cooled to 0°C. 0.06 mol of methacrylate phosphoryl chloride intermediate was dissolved in 35 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature between 0 and 5°C. After the addition was complete, the mixture was allowed to naturally warm to room temperature, and the reaction was continued with stirring for 6 hours. After the reaction was complete, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤ -0.095 MPa to obtain the polyether monohydroxy intermediate. The chemical structure of tetraethylene glycol is as follows:
[0047] ;
[0048] The 1H NMR spectrum of the polyether monohydroxy intermediate is shown below. Figure 3 As shown, the chemical structure is as follows:
[0049] .
[0050] (3) Under nitrogen protection, 0.12 mol of isophorone diisocyanate and 100 mL of anhydrous tetrahydrofuran were added to a dry four-necked flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel. Stirring was started, and the mixture was cooled to 0°C in an ice-water bath. 0.03 mol of bis(trimethylol)propane was dissolved in 120 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask. The dropping rate was controlled so that the temperature of the reaction solution did not exceed 10°C. After the addition was complete, 0.24 mmol of dibutyltin dilaurate was added as a catalyst. After stirring evenly, the mixture was heated to 45°C and stirred for 6 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound. The chemical structure of bis(trimethylol)propane is as follows:
[0051] .
[0052] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.16 mmol of dibutyltin dilaurate. The temperature of the reaction mixture was adjusted to 30°C. 0.06 mol of a siloxane monohydroxy intermediate was dissolved in 80 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 5 hours. Then, 0.065 mol of a polyether monohydroxy intermediate was dissolved in 70 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was then increased. The mixture was heated to 55℃ and stirred for 6 hours. After the reaction, it was cooled to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was cooled to 0℃ in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50℃ to constant weight to obtain the functional polyurethane acrylate. The 1H NMR spectrum of the functional polyurethane acrylate is shown below. Figure 4 As shown, the chemical structure is as follows:
[0053] .
[0054] The topcoat for UV-cured diamond Martian coating comprises the following components in parts by weight: 50 parts of silicone-fluorine modified sulfonic acid UV-curable resin, 16 parts of trifunctional acrylate monomer, 10 parts of difunctional acrylate monomer, 4 parts of monofunctional acrylate monomer, 12 parts of superhard wear-resistant powder, and 4 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2; the difunctional acrylate monomer is a dimethylolpropane triacrylate... Propylene glycol diacrylate; the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles and silicon carbide particles in a mass ratio of 4:7:9, with average particle sizes of 4 μm, 14 μm and 14 μm for diamond particles, zirconium oxide particles and silicon carbide particles, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1.
[0055] The preparation method of silicone-fluorine modified sulfonic acid type photocurable resin is as follows:
[0056] (1) Under nitrogen protection, 1.0 mol of glycidyl methacrylate, 1.0 mol of β-carboxyethyl acrylate, and 0.15 g of p-hydroxyanisole were added to a dry reaction flask equipped with a mechanical stirrer, thermometer, and reflux condenser. Stirring was started, nitrogen was introduced for 15 min, and the temperature was raised to 85 °C. Then, 2.5 g of triphenylphosphine was added, and the reaction was continued under nitrogen protection at 85 °C with stirring for 7 h. After the reaction was completed, the reaction solution was cooled to 60 °C and distilled under reduced pressure to constant weight under vacuum conditions ≤ -0.095 MPa to obtain the diacrylate hydroxyl compound intermediate. The 1H NMR spectrum of the diacrylate hydroxyl compound intermediate is shown below. Figure 5 As shown, the chemical structure is as follows:
[0057] .
[0058] (2) Under nitrogen protection, add 1.2 mol of phosphorus oxychloride and 600 mL of dichloromethane to a dry reaction flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Turn on the stirrer and cool down to 0°C. Dissolve 1.0 mol of 3-hydroxypropanesulfonic acid in 300 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 5°C. After the addition is complete, continue stirring at 0°C for 3 h. After the reaction is complete, remove the solvent and unreacted phosphorus oxychloride under reduced pressure at 45°C to obtain the intermediate 3-sulfonic acid propyl phosphate diacyl chloride.
[0059] The intermediate 3-sulfonyl propyl phosphate diacyl chloride, 400 mL of anhydrous dichloromethane, and 100 mL of anhydrous tetrahydrofuran were added to a reaction flask. After stirring until homogeneous, the mixture was cooled to 0°C. 1.0 mol of the diacrylate hydroxyl compound intermediate and 2.2 mol of the acid-binding agent triethylamine were dissolved in 180 mL of anhydrous dichloromethane and then added dropwise to the reaction solution. The dropping rate was controlled, and the reaction temperature was maintained between 0 and 5°C. After the addition was complete, the mixture was stirred at 0°C for 6 hours. After the reaction was completed, the mixture was filtered under nitrogen protection while cold. The filtrate was then concentrated by vacuum distillation at 35°C. One-third of the volume was used to obtain a concentrated solution. Under stirring, the concentrated solution was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath, stirred for 15 min, and allowed to stand for 2 h. The lower viscous phase was separated, and the upper petroleum ether supernatant was discarded. 20 mL of dichloromethane was added to the lower viscous phase, and after thorough stirring, 100 mL of anhydrous petroleum ether was added. After stirring and standing, the lower viscous phase was separated. The lower viscous phase was concentrated to constant weight under reduced pressure at 35°C and a vacuum degree ≤-0.095 MPa under nitrogen protection to obtain the diacrylate phosphoryl chloride intermediate. The 1H NMR spectrum of the diacrylate phosphoryl chloride intermediate is shown below. Figure 6 As shown, the chemical structure is as follows:
[0060] .
[0061] (3) Under nitrogen protection, 0.06 mol of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane, 80 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The temperature was lowered to 0°C. 0.06 mol of the diacrylate phosphoryl chloride intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature at 0~5°C. After the addition was complete, the temperature was naturally raised to room temperature, and the reaction was stirred for 6 h. After the reaction was completed, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤-0.095 MPa to obtain the diacrylate siloxane monohydroxy intermediate. The chemical structure of 1,3-bis(4-hydroxybutyl)-1,1,3,3-tetramethyldisiloxane is as follows:
[0062] ;
[0063] The 1H NMR spectrum of the diacrylate siloxane monohydroxy intermediate is shown below. Figure 7 As shown, the chemical structure is as follows:
[0064] .
[0065] Under nitrogen protection, 0.06 mol of 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol, 100 mL of anhydrous tetrahydrofuran, and 0.1 mol of triethylamine were added to a dry reaction flask. The mixture was cooled to 0°C. 0.06 mol of the diacrylate phosphoryl chloride intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The dropping rate was controlled to maintain the material temperature between 0 and 5°C. After the addition was complete, the mixture was allowed to warm naturally to room temperature, and the reaction was continued with stirring for 6 hours. After the reaction was complete, the mixture was filtered to remove the generated triethylamine hydrochloride. The filtrate was concentrated under reduced pressure to constant weight at 40°C and a vacuum degree ≤ -0.095 MPa to obtain the diacrylate fluoroether monohydroxy intermediate. The chemical structure of 1H,1H,8H,8H-octafluoro-3,6-diox-1,8-octanediol is as follows:
[0066] ;
[0067] The 1H NMR spectrum of the diacrylate fluoroether monohydroxy intermediate is shown below. Figure 8 As shown, the chemical structure is as follows:
[0068] .
[0069] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer, and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate to keep the temperature of the reaction solution below 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and then heat to 45°C. Maintain the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound. The chemical structure of 1,3,5-trihydroxyadamantane is as follows:
[0070] .
[0071] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask. Then, 0.05 mmol of dibutyltin dilaurate was added, and the temperature of the mixture in the reaction flask was adjusted to 30°C. 0.03 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 60 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 4 hours. Finally, 0.065 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 70 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was raised to 55℃, and the reaction was maintained at this temperature with stirring for 6 hours. After the reaction was completed, the temperature was lowered to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was placed in an ice-water bath and cooled to 0℃. After standing for 1 hour, the lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50℃ to constant weight to obtain the silicone-fluorine modified sulfonic acid type photocurable resin. The 1H NMR spectrum of the silicone-fluorine modified sulfonic acid type photocurable resin is shown below. Figure 9 As shown, the chemical structure is as follows:
[0072] .
[0073] The application process for the diamond Martian coating in this embodiment is as follows:
[0074] For high-density fiberboard (HDF, density ≥ 0.85 g / cm³) 3 The surface of the high-density fiberboard is sanded with 240 grit, and then coated (brushed) with a UV-cured diamond Mars coating primer at a coverage of 65 g / m². 2 After coating, the product is dried using a UV curing lamp with a UV energy of 150 mJ / cm². 2The primer is UV-cured to form a base coat; then the UV-cured diamond Martian coating is applied (brushed) onto the primer coat with a coverage of 30g / m². 2 After coating, the material is dried using a UV curing lamp with a UV energy of 500 mJ / cm². 2 The topcoat is formed after UV curing; after the topcoat is cured, it is cured at 25℃ for 12 hours to complete the application of the diamond Mars coating.
[0075] Example 2
[0076] The only difference between the diamond Mars coating of this embodiment and the diamond Mars coating of Example 1 is that the topcoat used in the preparation of the diamond Mars coating of this embodiment is composed of the following components in parts by weight: 55 parts of silicone-fluorine modified sulfonic acid type photocurable resin, 15 parts of trifunctional acrylate monomer, 8 parts of difunctional acrylate monomer, 5 parts of monofunctional acrylate monomer, 14 parts of superhard wear-resistant powder, and 4.5 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 4:3. The ester composition is as follows: the difunctional acrylate monomer is tripropylene glycol diacrylate; the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 4:8:10, with average particle sizes of 5 μm, 14 μm, and 14 μm, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1. The silicone-fluorine modified sulfonic acid type photocurable resin in this example is the same as the silicone-fluorine modified sulfonic acid type photocurable resin in Example 1.
[0077] Example 3
[0078] The only difference between the diamond Mars coating of this embodiment and the diamond Mars coating of Example 1 is that the topcoat used in the preparation of the diamond Mars coating of this embodiment is composed of the following components in parts by weight: 60 parts of silicone-fluorine modified sulfonic acid type photocurable resin, 11 parts of trifunctional acrylate monomer, 12 parts of difunctional acrylate monomer, 3 parts of monofunctional acrylate monomer, 16 parts of superhard wear-resistant powder, and 5 parts of photoinitiator; the trifunctional acrylate monomer is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 5:3. The ester composition is as follows: the difunctional acrylate monomer is tripropylene glycol diacrylate; the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:3; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 5:9:12, with average particle sizes of 6 μm, 16 μm, and 16 μm, respectively; the photoinitiator is a mixture of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of 2:1. The silicone-fluorine modified sulfonic acid type photocurable resin in this example is the same as the silicone-fluorine modified sulfonic acid type photocurable resin in Example 1.
[0079] Comparative Example 1
[0080] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the functional polyurethane acrylate in the light-cured diamond Mars coating primer used in the preparation of the diamond Mars coating of this example is as follows:
[0081] (1) This step is the same as step (1) of the preparation method of functional polyurethane acrylate in Example 1.
[0082] (2) This step is the same as step (2) of the preparation method of functional polyurethane acrylate in Example 1.
[0083] (3) Under nitrogen protection, add 0.12 mol of isophorone diisocyanate and 100 mL of anhydrous tetrahydrofuran to a dry four-necked flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of bis(trimethylol)propane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.24 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is completed, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0084] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.16 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.125 mol of a siloxane monohydroxy intermediate was dissolved in 150 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 5 hours, then the temperature was increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours. After the reaction was completed... The solution was cooled to room temperature, filtered to remove insoluble matter, and concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper supernatant was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50°C to constant weight to obtain the functionalized polyurethane acrylate. The chemical structure of the functionalized polyurethane acrylate is as follows:
[0085] .
[0086] Comparative Example 2
[0087] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the functional polyurethane acrylate in the light-cured diamond Mars coating primer used in the preparation of the diamond Mars coating of this example is as follows:
[0088] (1) This step is the same as step (1) of the preparation method of functional polyurethane acrylate in Example 1.
[0089] (2) This step is the same as step (2) of the preparation method of functional polyurethane acrylate in Example 1.
[0090] (3) Under nitrogen protection, add 0.12 mol of isophorone diisocyanate and 100 mL of anhydrous tetrahydrofuran to a dry four-necked flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of bis(trimethylol)propane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.24 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is completed, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0091] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.16 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.125 mol of the polyether monohydroxy intermediate was dissolved in 150 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 5 hours, then the temperature was increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours. After the reaction was completed, the temperature was lowered... The solution was cooled to room temperature, filtered to remove insoluble matter, and the filtrate was concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper supernatant was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50°C to constant weight to obtain the functionalized polyurethane acrylate. The chemical structure of the functionalized polyurethane acrylate is as follows:
[0092] .
[0093] Comparative Example 3
[0094] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the functional polyurethane acrylate in the light-cured diamond Mars coating primer used in the preparation of the diamond Mars coating of this example is as follows: the functional polyurethane acrylate prepared in Comparative Example 1 and the functional polyurethane acrylate prepared in Comparative Example 2 are stirred and mixed evenly at a mass ratio of 17.5:15.9.
[0095] Comparative Example 4
[0096] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the functional polyurethane acrylate in the light-cured diamond Mars coating primer used in the preparation of the diamond Mars coating of this example is as follows:
[0097] (1) This step is the same as step (1) of the preparation method of functional polyurethane acrylate in Example 1.
[0098] (2) This step is the same as step (2) of the preparation method of functional polyurethane acrylate in Example 1.
[0099] (3) Under nitrogen protection, add 0.12 mol of isophorone diisocyanate and 100 mL of anhydrous tetrahydrofuran to a dry four-necked flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of bis(trimethylol)propane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.24 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is completed, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0100] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.16 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.03 mol of a siloxane monohydroxy intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 4 hours. Then, 0.095 mol of a polyether monohydroxy intermediate was dissolved in 110 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was then increased. The mixture was heated to 55℃ and stirred for 8 hours. After the reaction, it was cooled to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was cooled to 0℃ in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50℃ to constant weight to obtain the functional polyurethane acrylate. The chemical structure of the functional polyurethane acrylate is as follows:
[0101] .
[0102] Comparative Example 5
[0103] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the functional polyurethane acrylate in the light-cured diamond Mars coating primer used in the preparation of the diamond Mars coating of this example is as follows:
[0104] (1) This step is the same as step (1) of the preparation method of functional polyurethane acrylate in Example 1.
[0105] (2) This step is the same as step (2) of the preparation method of functional polyurethane acrylate in Example 1.
[0106] (3) Under nitrogen protection, add 0.12 mol of isophorone diisocyanate and 100 mL of anhydrous tetrahydrofuran to a dry four-necked flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of bis(trimethylol)propane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.24 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is completed, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0107] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.16 mmol of dibutyltin dilaurate. The temperature of the reaction mixture was adjusted to 30°C. 0.09 mol of a siloxane monohydroxy intermediate was dissolved in 110 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 7 hours. Then, 0.035 mol of a polyether monohydroxy intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was then increased. The mixture was heated to 55℃ and stirred for 4 hours. After the reaction was complete, it was cooled to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring until homogeneous, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was cooled to 0℃ in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was dried under vacuum at 50℃ to constant weight to obtain the functional polyurethane acrylate. The chemical structure of the functional polyurethane acrylate is as follows:
[0108] .
[0109] Comparative Example 6
[0110] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the silicone-fluorine modified sulfonic acid type photocurable resin used in the preparation of the diamond Mars coating of this example is replaced with a silicone modified sulfonic acid type photocurable resin in the topcoat for preparing the photocurable diamond Mars coating. The preparation method of the silicone modified sulfonic acid type photocurable resin is as follows:
[0111] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0112] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0113] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0114] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0115] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.05 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.095 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 130 mL of anhydrous tetrahydrofuran and then added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 4 hours. The temperature was then increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours until the reaction was complete. The solution was then cooled to room temperature, filtered to remove insoluble matter, and concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the solution was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was vacuum dried at 50°C to constant weight to obtain the silicone-modified sulfonic acid type photocurable resin. The chemical structure of the silicone-modified sulfonic acid type photocurable resin is as follows:
[0116] .
[0117] Comparative Example 7
[0118] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the silicone-fluorine modified sulfonic acid type photocurable resin used in the preparation of the diamond Mars coating of this example is replaced with fluorine modified sulfonic acid type photocurable resin in the topcoat for photocuring diamond Mars coating. The preparation method of fluorine modified sulfonic acid type photocurable resin is as follows:
[0119] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat of Example 1;
[0120] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0121] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0122] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0123] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask, followed by 0.05 mmol of dibutyltin dilaurate. The temperature of the mixture in the reaction flask was adjusted to 30°C. 0.095 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 130 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was kept at 30°C with stirring for 4 hours. The temperature was then increased to 55°C and the mixture was kept at this temperature with stirring for 6 hours. After the reaction was complete, the mixture was cooled to room temperature. The insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40°C to 1 / 5 of its original volume to obtain a concentrate. 50 mL of 1,1,1,3,3,3-hexafluoroisopropanol was added to the concentrate, and after stirring thoroughly, it was added dropwise to 500 mL of anhydrous n-hexane. After the addition was complete, the mixture was cooled to 0°C in an ice-water bath and allowed to stand for 1 hour. The lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous n-hexane (50 mL × 2). Finally, it was vacuum dried at 50°C to constant weight to obtain the fluorinated sulfonic acid type photocurable resin. The chemical structure of the fluorinated sulfonic acid type photocurable resin is as follows:
[0124] .
[0125] Comparative Example 8
[0126] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat used in this comparative example is as follows: the silicone-modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat used in Comparative Example 6 and the fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat used in Comparative Example 7 are stirred and mixed evenly at a mass ratio of 1:1 to obtain the final product.
[0127] Comparative Example 9
[0128] The only difference between the diamond Mars coating of this comparative example and the diamond Mars coating of Example 1 is that the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Mars coating topcoat used in the preparation of this comparative example is as follows:
[0129] (1) This step is the same as step (1) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0130] (2) This step is the same as step (2) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0131] (3) This step is the same as step (3) of the preparation method of the silicone-fluorine modified sulfonic acid type photocurable resin in the photocurable diamond Martian coating topcoat of Example 1;
[0132] (4) Under nitrogen protection, add 0.09 mol of isophorone diisocyanate and 80 mL of anhydrous tetrahydrofuran to a dry flask equipped with a mechanical stirrer, thermometer and constant pressure dropping funnel. Start stirring and cool to 0°C in an ice-water bath. Dissolve 0.03 mol of 1,3,5-trihydroxyadamantane in 120 mL of anhydrous tetrahydrofuran and add it dropwise to the reaction flask. Control the dropping rate so that the temperature of the reaction solution does not exceed 10°C. After the addition is complete, add 0.18 mmol of dibutyltin dilaurate as a catalyst. Stir evenly and heat to 45°C. Keep the temperature and stir for 6 h. After the reaction is complete, cool to room temperature to obtain a tetrahydrofuran solution of the isocyanate-terminated compound.
[0133] A tetrahydrofuran solution of the isocyanate-terminated compound was added to the reaction flask. Then, 0.05 mmol of dibutyltin dilaurate was added, and the temperature of the mixture in the reaction flask was adjusted to 30°C. 0.06 mol of a diacrylate siloxane monohydroxy intermediate was dissolved in 90 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask, maintaining the temperature at 30–35°C. After the addition was complete, the mixture was stirred and kept at 30°C for 6 hours. Finally, 0.035 mol of a diacrylate fluoroether monohydroxy intermediate was dissolved in 40 mL of anhydrous tetrahydrofuran and added dropwise to the reaction flask. The temperature was raised to 55℃, and the reaction was maintained at this temperature with stirring for 5 hours. After the reaction was completed, the temperature was lowered to room temperature, and the insoluble matter was removed by filtration. The filtrate was concentrated under reduced pressure at 40℃ to 1 / 5 of its original volume to obtain a concentrate. 50 mL of anhydrous tetrahydrofuran was added to the concentrate, and after stirring evenly, it was added dropwise to 500 mL of anhydrous petroleum ether. After the addition was complete, the mixture was placed in an ice-water bath and cooled to 0℃. After standing for 1 hour, the lower viscous phase was separated, and the upper clear liquid was discarded. The lower viscous phase was washed twice with anhydrous petroleum ether (50 mL × 2). Finally, it was vacuum dried at 50℃ to constant weight to obtain the silicone-fluorine modified sulfonic acid type photocurable resin. The chemical structure of the silicone-fluorine modified sulfonic acid type photocurable resin is as follows:
[0134] .
[0135] Experimental Example 1
[0136] To investigate the basic properties of the UV-cured diamond Mars coating primers used in Examples 1 and 1-5, the storage stability, adhesion, solvent wiping resistance, and abrasion resistance of the UV-cured diamond Mars coating primers in Examples 1 and 1-5 were tested. The sedimentation stability test method was as follows: the prepared primer sample was poured into a 50mL stoppered graduated cylinder to full volume, sealed, and placed in a 30°C constant temperature incubator. Observations were made every 24 hours, and the number of days until the first visible sediment appeared at the bottom of the graduated cylinder was recorded. For testing hardness, adhesion, solvent wiping resistance, and abrasion resistance, the primer was first prepared into a coating, as follows: For high-density fiberboard (HDF, density ≥ 0.85 g / cm³),... 3 The surface of the high-density fiberboard is sanded with a 240-grit finish, and then a UV-cured diamond Mars coating primer is applied to the sanded surface at a coverage of 65 g / m². 2 After coating, the product is dried using a UV curing lamp with a UV energy of 150 mJ / cm². 2 After UV curing, the primer layer is formed and then cured at 25°C for 12 hours before being tested for adhesion, solvent wiping resistance and abrasion resistance.
[0137] Adhesion was tested according to GB / T 5210-2006 "Paints and Varnishes - Pull-off Adhesion Test". A 20mm diameter test column was used, and a two-component epoxy adhesive was used to bond the test column to the coating surface. The test was conducted on a universal testing machine at a tensile speed of 1mm / min. The maximum tensile force at which the coating failed was recorded, and the pull-off adhesion was calculated. MEK wiping resistance was tested according to GB / T 23989-2009 "Coatings - Solvent Resistance Wiping Test". A degreased cotton ball soaked in methyl ethyl ketone (MEK) solvent was used to wipe the coating surface bidirectionally at a frequency of 1 swipe / second. The number of unidirectional wipings when the coating surface exposed the substrate was recorded. Abrasion resistance was tested according to GB / T 1768-2006 "Determination of Abrasion Resistance of Paints and Varnishes - Rotary Rubber Grinding Wheel Method". A Taber 5135 abrasion tester was used, with a CS-10 rubber grinding wheel and a 500g weight loaded. The mass loss of the coating after 1000 revolutions was measured, and the unit is mg. Before each test, the grinding wheel was pre-polished with S-11 sandpaper for 50 revolutions. Three parallel samples were tested, and the average value was taken.
[0138] The stability and mechanical properties of the primers used in Example 1 and Comparative Examples 1-5 for the photocurable diamond Martian coating are shown in Table 1.
[0139] Table 1. Test results of stability and mechanical properties of primer for UV-cured diamond Martian coating.
[0140]
[0141] As can be seen from the test results in Table 1, the primer for the light-cured diamond Mars coating used in this invention has good settling stability, adhesion, solvent wiping resistance and abrasion resistance, and exhibits good overall performance in terms of bottom anchoring and load bearing.
[0142] As shown in Example 1 and Comparative Examples 1-3, when only siloxane side chains are introduced into the functional polyurethane acrylate without polyether side chains, the coating exhibits poor sedimentation stability and adhesion, and reduced abrasion resistance. When only polyether side chains are introduced without siloxane side chains, the coating also shows poor sedimentation stability, and its solvent resistance and abrasion resistance deteriorate. Siloxane segments have low surface energy and excellent wettability, enabling them to migrate well to the inorganic powder interface to form a dense coating layer, effectively preventing powder agglomeration and sedimentation, while enhancing the interfacial spreading and adhesion of the coating to the substrate. Polyether segments, on the other hand, possess high flexibility and polar ether bonds, which can regulate the microstructure of the resin network, providing good stress release capabilities and endowing the coating with toughness to resist dynamic friction and solvent swelling. Comparative Example 9 physically blends resins containing only siloxane segments and resins containing only polyether segments. Due to the poor thermodynamic compatibility of the two, microphase separation easily occurs after curing, making it difficult to construct a continuous and uniform dispersion and stress transfer network.
[0143] As shown in Example 1 and Comparative Examples 4-5, when the ratio of siloxane side chains to polyether side chains in the functional polyurethane acrylate is changed, the sedimentation stability of the coating deteriorates, and both adhesion and abrasion resistance cannot be simultaneously achieved. This further demonstrates that around the rigid crosslinked core constructed from isophorone diisocyanate and bis(trimethylol)propane, the ratio of siloxane side chains to polyether side chains is crucial for balancing the powder dispersion stability of the resin system, the wetting and anchoring force of the substrate, and the abrasion resistance of the coating itself.
[0144] In summary, the primer for the light-cured diamond Mars coating provided in this invention is made by mixing a functional polyurethane acrylate with bis(trimethylol)propane as the core skeleton and containing sulfonic acid groups, siloxane side chains and polyether side chains in its molecular structure with epoxy acrylate, a trifunctional monomer compounded with pentaerythritol ethoxytriacrylate and trimethylolpropane propoxytriacrylate, a bifunctional monomer compounded with tripropylene glycol diacrylate and ethoxylated bisphenol A diacrylate, and superhard wear-resistant powder. It has good storage stability, adhesion, solvent resistance and wear resistance, providing a solid and stable underlying support for the topcoat.
[0145] Experiment Example 2
[0146] To examine the overall performance of the photocurable diamond Mars coating topcoat used in each embodiment and Comparative Examples 6-9, coatings were prepared using the photocurable diamond Mars coating topcoat used in each embodiment and Comparative Examples 6-9. The preparation methods are as follows: For high-density fiberboard (HDF, density ≥ 0.85 g / cm³), the coatings were prepared using the following methods: 3 The surface of the high-density fiberboard is sanded with 240 grit, and then coated (brushed) with a UV-cured diamond Mars coating primer at a coverage of 65 g / m². 2 After coating, the product is dried using a UV curing lamp with a UV energy of 150 mJ / cm². 2 The primer is cured by UV to form a base coat; then the topcoat is applied (brushed) onto the primer coat, with a coverage of 30g / m². 2 After coating, the material is dried using a UV curing lamp with a UV energy of 500 mJ / cm². 2 After UV curing, the topcoat layer is formed and cured at 25℃ for 12 hours before testing for adhesion, hardness, abrasion resistance, and solvent resistance. To test the adhesion of the superhard abrasion-resistant powder, the tinplate surface is sanded with a 240-grit finish, and then the topcoat is applied (brushed) to the sanded tinplate surface at a coverage of 30 g / m². 2 After coating, the material is dried using a UV curing lamp with a UV energy of 500 mJ / cm². 2After UV curing, the topcoat layer is formed. After curing at 25℃ for 12 hours, the adhesion strength of the superhard wear-resistant powder is tested.
[0147] The adhesion test was conducted according to the requirements of standard GB / T 5210-2006. A 20mm diameter test column was adhered to the cured coating surface. After curing, a tensile force was applied perpendicular to the board surface until the coating was pulled off, and the maximum tensile force at failure was recorded. The hardness test was conducted according to the requirements of standard GB / T 6739-2006. The abrasion resistance test was conducted according to the requirements of standard GB / T 1768-2006. A Taber abrasion tester was used with a loading pressure of 5N. The diamond Martian coating was rotated and rubbed with P180 grit (180 mesh) abrasive cloth. The abrasive paper was replaced every 500 revolutions to avoid abrasion and test deviation. During the test, the coating was divided into four equal parts. The test was stopped when three parts showed a 95% exposure rate (the exposure rate is defined as the proportion of the area of the underlying substrate exposed when the coating surface is worn through to the total test area). The corresponding number of rotations was recorded as the abrasion resistance test result. Solvent resistance was tested according to standard GB / T The acetone wiping test specified in GB / T 23989-2009 involves smearing a cotton swab with acetone and applying a force of 1N to the coating surface, wiping back and forth at a rate of 60 swipes per minute until the primer is clearly exposed (film breakage). The number of swipes is recorded as the solvent resistance test result. The test method for the adhesion strength of the superhard abrasion-resistant powder is as follows: the cured coating sample (substrate is tinplate) is cut into 10cm × 10cm pieces with an accuracy of 0.01m. The initial mass m1 of the topcoat coating on the test specimen was weighed using an analytical balance (calculated by the mass difference between the specimen before and after coating). The specimen was placed coating-side down on the pad of the impact testing machine, and a 1kg hammer was dropped to impact the back of the specimen, subjecting the coating surface to instantaneous tension. After the impact, the debris loosened by the impact was gently brushed away with a soft brush, and the specimen was weighed again to calculate the remaining mass m2 of the topcoat coating. The impact dust removal rate was calculated as (m1-m2) / m1×100%. The lower the dust removal rate, the stronger the interfacial anchorage of the ultra-hard powder in the coating. The test conditions were the same for all samples, and each sample was tested 3 times. The average value was calculated after the test.
[0148] Table 2 shows the test results of adhesion, hardness, abrasion resistance, solvent resistance, and adhesion strength of the superhard abrasion-resistant powder for the topcoat used in each embodiment and comparative example of the diamond Mars coating. Images of the diamond Mars coating prepared with the photocurable diamond Mars coating topcoat of Example 1 before and after the abrasion resistance test are shown below. Figure 10 and Figure 11 As shown.
[0149] Table 2. Comprehensive performance test results of diamond Martian coatings prepared with topcoat for UV-cured diamond Martian coating.
[0150]
[0151] As can be seen from the test results in Table 2, the topcoat for the light-cured diamond Mars coating provided by the present invention has good adhesion, hardness, abrasion resistance, solvent resistance and low impact powdering rate, showing good comprehensive performance.
[0152] Comparing the test results of Example 1 and Comparative Examples 6-8, it can be seen that when only organosilicon segments are introduced into the resin and organofluorine segments are lacking, the solvent resistance of the coating deteriorates and the powdering rate increases; when only organofluorine segments are introduced and organosilicon segments are lacking, the adhesion of the coating deteriorates, the hardness decreases, and the powdering rate increases. The silicon-oxygen bonds in the organosilicon segments have high bond energy and flexibility, which can form effective molecular chain entanglement and polar interaction at the interface between the coating and the primer layer, thereby helping to improve the wettability and adhesion anchoring force of the coating to the substrate; at the same time, the introduction of organosilicon segments can adjust the flexibility and cross-linking density of the resin network, which helps to absorb and disperse external impacts and reduce the tendency of wear-resistant powder particles to de-adhede under stress. Organic fluorine segments, due to the low polarizability and surface free energy of carbon-fluorine bonds, preferentially migrate to the coating surface and internal micropore interface during curing, forming a dense, low surface energy barrier. This helps to block the penetration and swelling damage of solvent molecules such as acetone. Simultaneously, this surface enrichment effect also helps to enhance the density of the resin's coating on the wear-resistant powder particles. However, when only organic fluorine segments are present, their excessively low surface energy leads to insufficient spreading and penetration of the resin into the substrate, weakening interfacial adhesion and macroscopically manifesting as poor adhesion. When only organosilicon segments are present, the lack of a dense surface barrier from fluorine segments results in deteriorated solvent resistance. In Comparative Example 8, when the two were physically blended, the poor thermodynamic compatibility between the silicone and fluorine segment resins easily led to the formation of a micro-phase separation structure after curing, making it difficult to construct a continuous, uniform, and dense network. This resulted in interfacial stress concentration and solvent penetration channels, leading to poor overall performance.
[0153] Comparing the test results of Example 1 and Comparative Example 9, it can be seen that when the ratio of organosilicon segments to organofluorine segments in the resin is changed, the coating exhibits poor abrasion resistance and solvent resistance, and a high impact powdering rate. This result indicates that around the rigid crosslinked core constructed from isophorone diisocyanate and 1,3,5-trihydroxyadamantane, a suitable ratio of organosilicon to organofluorine side chains is necessary to achieve a good balance between the cohesive strength of the resin system, substrate wettability, and powder anchoring force.
[0154] In summary, the photocurable diamond Mars coating topcoat provided in this invention is made by mixing a photocurable resin with adamantane as the core skeleton and containing sulfonic acid groups, organosilicon segments and organofluorine segments in its molecular structure with an ultra-hard wear-resistant powder composed of diamond particles, zirconium oxide particles and silicon carbide particles. It has high adhesion, hardness, good wear resistance, solvent resistance and filler anchoring force.
[0155] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be pointed out that, due to the limitations of written expression and the objective existence of infinite specific structures, those skilled in the art can make several improvements, modifications, or variations without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.
Claims
1. A diamond Mars coating, characterized in that, It is composed of a diamond Mars coating primer layer and a topcoat layer; wherein, the primer layer is obtained by UV curing of the primer, and the topcoat layer is obtained by UV curing of the topcoat; The primer is composed of the following components in parts by weight: 30-40 parts functional polyurethane acrylate, 9-12 parts epoxy acrylate, 25-36 parts multifunctional acrylate monomer, 18-25 parts superhard wear-resistant powder, and 4-5 parts photoinitiator; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles; the multifunctional acrylate monomer is composed of trifunctional acrylate monomer and difunctional acrylate monomer; based on the total mass of the multifunctional acrylate monomer, the trifunctional acrylate monomer accounts for 30%-40%, and the difunctional acrylate monomer accounts for 60%-70%; the chemical structure of the functional polyurethane acrylate is as follows: ; The topcoat is composed of the following components in parts by weight: 50-60 parts of silicone-fluorine modified sulfonic acid photocurable resin, 11-16 parts of trifunctional acrylate monomer, 8-12 parts of difunctional acrylate monomer, 3-5 parts of monofunctional acrylate monomer, 12-16 parts of superhard wear-resistant powder, and 4-5 parts of photoinitiator; the superhard wear-resistant powder is composed of diamond particles, zirconium oxide particles, and silicon carbide particles in a mass ratio of 4-5:7-9:9-12, and the chemical structure of the silicone-fluorine modified sulfonic acid photocurable resin is as follows: 。 2. The diamond Mars coating according to claim 1, characterized in that, The trifunctional acrylate monomer in the primer is composed of pentaerythritol ethoxylated triacrylate and trimethylolpropane propoxylated triacrylate in a mass ratio of (3~9):(1~5); the difunctional acrylate monomer is composed of tripropylene glycol diacrylate and ethoxylated bisphenol A diacrylate in a mass ratio of (5~7):(2~4).
3. The diamond Mars coating according to claim 2, characterized in that, The pentaerythritol ethoxylated triacrylate is pentaerythritol ethoxy(5) triacrylate.
4. The diamond Mars coating according to claim 2, characterized in that, The ethoxylated bisphenol A diacrylate is 10(ethoxy)bisphenol A diacrylate.
5. The diamond Mars coating according to claim 1, characterized in that, The mass ratio of diamond particles, zirconium oxide particles and silicon carbide particles in the primer is (3~5):(5~9):(10~12).
6. The diamond Mars coating according to claim 1, characterized in that, The average particle sizes of the diamond particles, zirconium oxide particles, and silicon carbide particles in the primer are 10~20μm, 20~40μm, and 20~40μm, respectively.
7. The diamond Mars coating according to claim 1, characterized in that, The trifunctional acrylate monomer in the topcoat is composed of ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate in a mass ratio of 3:2 to 5:3; the difunctional acrylate monomer is dipropylene glycol diacrylate; and the monofunctional acrylate monomer is composed of tetrahydrofurfuryl acrylate and isobornyl acrylate in a mass ratio of 1:2 to 1:
3.
8. The diamond Mars coating according to claim 1, characterized in that, The average particle sizes of the diamond particles, zirconium oxide particles, and silicon carbide particles in the topcoat are 4~8μm, 10~16μm, and 10~16μm, respectively.
9. A construction process for a diamond Martian coating as described in any one of claims 1-8, characterized in that, Includes the following steps: The wood substrate is surface treated, and then the primer is applied to the treated wood substrate surface. After light curing, the topcoat is applied, and after light curing, a diamond Mars coating is obtained.
10. The construction process of the diamond Mars coating according to claim 9, characterized in that, The application rate of the primer is 60~100g / m². 2 The energy for UV curing is 100~200 mJ / cm. 2 The application rate of the topcoat is 18~35g / m². 2 The energy for UV curing is 450~550 mJ / cm. 2 .
Citation Information
Patent Citations
Preparation method of light-cured composite wear-resistant anticorrosive coating and workpiece
CN112480791A